History as a science : the philosophy of R.G. Collingwood - Dussen, W. J. van der, (Religious Studies, Theology and Philosophy E-Books Online, Collection 2020, ISBN: 9789004419094., 2020)
"Since its appearance in 1981, History as a Science by Jan van der Dussen has been welcomed as a coherent and comprehensive study of the many aspects of Collingwood's philosophy of history, including its development and reception. The book was the first to pay attention to Collingwood's unpublished manuscripts, and to his work as an archaeologist and historian, herewith opening up a new angle in Collingwood studies. The republication of this volume meets an increasing demand to make the book available for future Collingwood scholars, and people interested in Collingwood's philosophy. The present edition of History as a Science includes updated references to the published manuscripts and an added preface".